Comparison between the dynamic and initial creep response of porcine and human lumbar intervertebral discs - Araújo, Ângelo Rafael Gomes (2015)
The study of mechanical properties of intervertebral disc (IVD) is important for the evaluation of disc implants. To determine these properties, several animal spine models were used. The goal of this work is to determine and compare the dynamic stiffness coefficient (K-d) and initial creep behavior of porcine intervertebral disc with the human ones. Porcine lumbar "motion segments" were subjected to 1200 cycles of axial compressive loading at 1 Hz, and a mean load of 500 N. The results were fitted with a mathematical model. The Kd values are in same magnitude as the previously reported for human. The model showed a good adjust to the initial creep behavior and the obtained parameters present the same magnitude as the human discs, with exception of time constant. This work revealed that porcine MS is an interesting model to study both the dynamic behavior and initial creep response of human disc.